phân tích đa thức thành nhân tử x(x+2)(x+3)(x+5)+9

phân tích đa thức thành nhân tử
x(x+2)(x+3)(x+5)+9

0 thoughts on “phân tích đa thức thành nhân tử x(x+2)(x+3)(x+5)+9”

  1. Đáp án:

     $(x^2+5x+3)^2$

    Giải thích các bước giải:

     $x.(x+2).(x+3).(x+5)+9$

    $=[x.(x+5)].[(x+2).(x+3)]+9$

    $=[x^2+5x].[x^2+5x+6]+9$

    đặt $t=x^2+5x$ ta có:

    $t.(t+6)+9$

    $=t^2+6t+9$    

    $=t^2+2.t.3+3^2 $

    $=(t+3)^2$     (1)

    thay $ t= x^2+5x$ vào (1) ta được:

    $(x^2+5x+3)^2$

    Reply

Leave a Comment